Phase-cycled simultaneous multi-slice balanced SSFP imaging with CAIPIRINHA for efficient banding reduction - Wang, Yi (Magn Reson Med, 2015)
PURPOSE: To present a time-efficient technique for banding reduction in balanced steady-state free precession (bSSFP) imaging by utilizing phase-cycled simultaneous multi-slice (SMS) acquisition with CAIPIRINHA (controlled aliasing in parallel imaging results in higher acceleration). THEORY: The proposed technique exploits the inherent phase modulation of SMS imaging with CAIPIRINHA to acquire multiple phase-cycled images, which can be combined for efficient banding reduction within the same scan time of a single-band bSSFP scan. METHODS: Bloch equation simulation, phantom and in vivo brain, abdominal and cardiac imaging experiments were performed on healthy volunteers at 3T using multi-channel head and body array coils with SMS acceleration factors of two to four. The performance of banding reduction was quantitatively evaluated based on the percent ripple of signal distribution and signal-to-noise ratio (SNR) efficiency in both phantom and human studies. RESULTS: The banding artifact was successfully removed or suppressed using phase-cycled SMS bSSFP imaging across SMS factors of two to four. The performance of banding reduction improved with higher SMS factors along with increased SNR efficiency. CONCLUSION: Phase-cycled SMS bSSFP with CAIPIRINHA is a promising technique for efficient band reduction in bSSFP without prolonged scan time. Further evaluation of this technique in clinical applications is warranted.